Pam and Reid Allen letter to Thomas Kent regarding fall field reports, December 1, 1994 - Allen, Pamet al; Allen, Reid I.et al (1994)
Letter from Pam and Reid Allen to Thomas Kent dated December 1, 1994. This letter lists bird sightings for August through November 1994. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1994. Plustek - flatbed